Pengaruh Work Life Balance dan Pemberian Insetif Terhadap Loyalitas Tenaga Kependidikan Universitas Pattimura yang dimediasi oleh Kepuasan Kerja - Pentury, Gerrit M.; Leuhary, Ferdy; Chandra, Felix (Universitas Yapis Papua, 2024)
This study examines the impact of Work-life balance and incentives on job satisfaction and work loyalty among the educational staff of Pattimura University. It also explores the mediating role of job satisfaction in the relationship between Work-life balance, incentives, and loyalty. Using a mixed-method approach, the study collects primary and secondary data through surveys and questionnaires. Path analysis is applied for inferential data analysis. Findings reveal that Work-life balance and incentives significantly influence job satisfaction and work loyalty. Additionally, job satisfaction mediates the relationship between both Work-life balance and incentives with loyalty.